Transition and transformation Victor Sjöström in Hollywood 1923-1930 - Florin, Bo 1961- (Film culture in transition, 2020)
In 1923, the film director Victor Seastrom (né Sjöström), then Sweden's most renowned filmmaker, was recruited to Hollywood by Goldwyn Pictures, where he made eight silent pictures and one talkie in seven years, among them a 1926 version of 'The Scarlet Letter'. What elements of Swedish cinema did he bring with him to the States, and how were these techniques transformed by Hollywood? This is the first book-length study dedicated to the films of Sjöström (1879-1960) and how he functioned in the studio system of 1920s Hollywood. Bo Florin explores the ways the director applied his austere and naturalistic film style in a radically different context and discusses how his films were received in Hollywood